Strengthening MSME Communication Networks Through Student Work Practices in the Kediri City Government - Satriyo, Bagus; Damianto; Khotimah, Dwi Khusnul; Widyaningrum, Berliana Nur (Journal Management & Economics Review (JUMPER), 2024)
The purpose of this research is to explore the role of students in strengthening the communication network of Micro, Small, and Medium Enterprises (MSMEs) in Kediri City through Student Work Practice (PKM) in the Protocol and Leadership Communication Section. This research identifies the challenges faced by MSMEs in marketing local products, especially batik and ikat weaving, as well as the importance of effective communication. The method used is a descriptive qualitative approach with data collection through interviews, direct observation, and document analysis for 45 days. The results of the study show that student involvement in public relations activities can improve the marketing strategy of MSMEs and strengthen government support. The importance of collaboration between students and MSME actors to overcome marketing challenges and strengthen the image of local products, especially batik and ikat weaving in Kediri City. The participation of students contributes to creating synergy between MSME actors and the government in facing the challenges of the global market. Thus, PKM not only functions as a learning forum for students, but also as a real contribution to local economic development.